A unique presentation of destructive shoulder arthropathy in the chronic phase of chronic myeloid leukaemia. (June 2019) - Howard, Joshua; Mackenzie, Benedict; Nicholson, Toby; Connolly, Sylvia; Parmar, Rishee
We present a previously unreported case of rapidly progressing, destructive shoulder arthropathy as an initial presentation of chronic phase chronic myeloid leukaemia. This patient initially presented to clinic for consideration of an arthroplasty for symptom relief; however, her loss to follow-up yielded a rapid progression of her symptoms. Bone marrow aspirate and targeted biopsy of the humeral head excluded blast cell crisis, in contrast to previously reported cases. She was treated conservatively with medical management of her underlying disease. Although leukaemic arthritis is a recognized phenomenon, chronic myeloid leukaemia is not known to cause bone destruction of this kind, particularly in the absence of blast crisis. Medical treatment with a tyrosine kinase inhibitor provided a dramatic improvement in our patient's pain, without the risk of attempted arthroplasty in unknown bone quality. We describe a unique presentation of severe bone destruction as a manifestation of chronic myeloid leukaemia in the absence of blast crisis. This should be considered as a rare differential diagnosis in joint arthropathy and may be appropriately managed initially with medical therapy, whereas future arthroplasty comprises uncharted territory in unknown bone quality.